1988
DOI: 10.1037/0096-1523.14.1.60
|View full text |Cite
|
Sign up to set email alerts
|

Dividing attention between the hands and the head: Performance trade-offs between rapid finger tapping and verbal memory.

Abstract: whether this task combination would reveal a specialized resource responsible for coordinating motor outputs when at least one of those outputs involves speech. A second, related purpose was to demonstrate the importance of manipulating task priority when attempting to determine the resource requirements of a task.The rationale underlying our approach and its methodology derives from the multiple resources model of Navon and Gopher (1979), which builds on earlier constructs about divided attention (Norman & B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
30
0

Year Published

1989
1989
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(32 citation statements)
references
References 37 publications
2
30
0
Order By: Relevance
“…For example, Hirst and Kalmar (1987) used time-sharing to refer to rapid switching between the processing oftwo tasks. In contrast, time-sharing in the present paper is used along the tradition followed by Gopher (1993), Friedman, Polson, andDafoe (1988), Moray (1967), andWickens (1990). Here, time-sharing refers to the simultaneous processing of two or more tasks.…”
mentioning
confidence: 99%
“…For example, Hirst and Kalmar (1987) used time-sharing to refer to rapid switching between the processing oftwo tasks. In contrast, time-sharing in the present paper is used along the tradition followed by Gopher (1993), Friedman, Polson, andDafoe (1988), Moray (1967), andWickens (1990). Here, time-sharing refers to the simultaneous processing of two or more tasks.…”
mentioning
confidence: 99%
“…They assumed that if word reading required storage in short-term memory, the phonological processing center would be activated. Friedman et al (1988) postulated that hemisphere-specific competition for cognitive processing resources would exist in the use of the left hemisphere for both verbal processing and contralateral motor control. Due to this competition, it is possible that the hemisphere specialization has an influence on muscle activity.…”
Section: Groupingmentioning
confidence: 99%
“…It has been suggested that the cerebral hemispheres represent two structurally defined resources (Friedman & Poison, 1981;Friedman, Poison, & Dafoe, 1988;Kinsbourne & Cook, 1971;Wickens, 1980;Wickens, Mountford, & Schreiner, 1981). According to these hypotheses, dual-task decrements in performance may sometimes reflect intrahemispheric competition for information processing resources (Friedman & Poison, 1981;Friedman, Poison, & Dafoe, 1988;Kinsbourne & Cook, 1971).…”
Section: -3mentioning
confidence: 99%
“…It is has been suggested that dual-task decrements in performance (a decrease in ability from single-to multiple-task situations) are the result of competition between tasks for particular resources (Friedman, Poison, & Dafoe, 1988;Kinsbourne & Hicks, 1978;Navon & Gopher, 1979;Wickens, 1980Wickens, , 1984Wickens, , 1991Wickens, , 1992, with resources being defined variously in terms of processing stages, codes of processing, input modality (See Wickens, 1991Wickens, , 1992, as well as in structure (Friedman & Poison, 1981;Friedman, Poison & Dafoe, 1988;Kinsbourne & Hicks, 1978;Kinsbourne & Hiscock, 1983). Generally, to the extent that two concurrently performed tasks compete for the same resources, decreases in performance will be predicted to occur (See Fracker & Wickens, 1989;Lane, 1982 for more detailed discussions of resource theory).…”
Section: Introductionmentioning
confidence: 99%